The theory of planned behavior: Factors influencing the consumption intentions of Chinese international students - LinPeng, Xiang; Xuan, Cai; Jun, Li; Karim, Rosman Bin (Edelweiss Applied Science and Technology, 2025)
With the rapid economic development and increasing income levels among residents, China has become the world’s largest source of international students, and the demand for studying abroad remains strong. Although the employment advantages of overseas university degrees are no longer as significant, and cross-border study abroad involves numerous risks, the scale of studying abroad has continued to grow substantially in recent years. Based on the theory of planned behavior, this study focuses on Chinese international students as its research subjects. It examines the influence of three key factors—subjective norms, perceived behavioral control, and behavioral intentions—on the consumption intentions of international students. It also employs a questionnaire survey method for empirical research. The results indicate that subjective norms, perceived behavioral control, and behavioral attitudes of Chinese international students have a significant positive impact on their consumption intentions. Additionally, behavioral attitudes serve as a mediating factor between subjective norms and consumption intentions, as well as between perceived behavioral control and consumption intentions. Based on these findings, the study proposes relevant recommendations across three levels: national policy, enterprise support, and student perspectives, to provide guidance for Chinese international students’ decisions regarding studying abroad.